ZINCO EM ALGUNS SOLOS DE PIRACICABA – AVALIAÇÃO POR TESTES BIOLÓGICOS - Sobrinho, M. O. C. Brasil; Freire, O.; Silveira, R. I. (REVISTA DE AGRICULTURA, 2020)
ZINCO EM ALGUNS SOLOS DE PIRACICABA – AVALIAÇÃO POR TESTES BIOLÓGICOS